Associativity in the Cerro de Montevideo in the Years of the Meat Processing Industry, Uruguay, 1920-1950; [la Asociatividad en el Cerro de Montevideo en Los Años de la Industria Frigorífica, Uruguay, 1920-1950] - Tecpan-Flores, S (Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura, 2023)
This article is about the associative process that took place in Villa del Cerro in Montevideo, between 1920s and 1950s, a period of boom and crisis of the meat-packing processing industry that was installed in it, trying to make it relevant. It means, the relationships between workspaces and neighborhood, and the influence of both dimensions in the formation of worker’s identity. The reconstruction of this associative process was carried out from secondary sources, local press and a large set of texts based on testimonies, observing that the numerous and diverse organizations that were created in the Cerro nurtured the experiences and repertoires of their neighbors and workers, contributing meaningfully to the formation of their identity. © 2023 Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura. All rights reserved.